2012
DOI: 10.1177/0269094211429654
|View full text |Cite
|
Sign up to set email alerts
|

Exploring entrepreneurial skills and competencies in farm tourism

Abstract: Is a PhD student in the School of Sport, Tourism & The Outdoors, at the University of Central Lancashire, Preston, UK. Investigating farm tourism and the supply of farm based recreation, his project critically appraises the nature and extent of the entrepreneurial competencies, activities and needs of farmers as providers of rural tourism products and experiences. Locating the analysis within contemporary UK and EU rural development and diversification policies. Richard Sharpley Exploring Entrepreneurial Skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 47 publications
(44 reference statements)
9
78
0
4
Order By: Relevance
“…The result indicated that a positive relationship exists between entrepreneurial skill with the entrepreneurial intention of Nigerian students (ß=0.29; t =5.297; p = 0.00), thereby supporting H1. The finding of this study is consistent with previous studies (Fini et al, 2009;Liñán, 2008;Phelan & Sharpley, 2012;Pyysiainen et al, 2006). The result also revealed that a positive relationship exists between environmental factors with entrepreneurial intention of Nigerian students (ß= 0.84; t =1.556; p = 0.06).…”
Section: Structural Model Results (Pls Path With Moderator)supporting
confidence: 94%
See 1 more Smart Citation
“…The result indicated that a positive relationship exists between entrepreneurial skill with the entrepreneurial intention of Nigerian students (ß=0.29; t =5.297; p = 0.00), thereby supporting H1. The finding of this study is consistent with previous studies (Fini et al, 2009;Liñán, 2008;Phelan & Sharpley, 2012;Pyysiainen et al, 2006). The result also revealed that a positive relationship exists between environmental factors with entrepreneurial intention of Nigerian students (ß= 0.84; t =1.556; p = 0.06).…”
Section: Structural Model Results (Pls Path With Moderator)supporting
confidence: 94%
“…By this, entrepreneurs are expected to have a balanced skills to successfully run their business as supported by (Wagner, 2003(Wagner, , 2006. Numerous studies such as (Fini, Grimaldi, Marzocchi, & Sobrero, 2009;Liñán, 2008;Phelan & Sharpley, 2012;Pyysiainen et al, 2006) have established a significant relationship between entrepreneurial skill and entrepreneurial intention. Thus, the present study hypothesized that: H1: Entrepreneurial skill will be positively related to entrepreneurial intention…”
Section: Entrepreneurial Skills and Entrepreneurial Intentionmentioning
confidence: 99%
“…In the framework of entrepreneurship, competencies are specifically related to the creation, survival and/ or growth of a business [15]. Researches shows that entrepreneurial competencies are necessary for the development and survival of an organization [14,16]. Reference [17] in their evaluation of the impact of entrepreneurial characteristics on the performance of small scale manufacturing industries in Nigeria established that majority of the Personal Entrepreneurial Competency (PEC) of the respondents made negative contribution on the sales revenue, only demand for efficiency and product quality, information seeking; and systematic planning and monitoring had positive impact.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These attributes include attitudes, values, beliefs, knowledge, skills, abilities, personality, wisdom, expertise (social, technical, and managerial), mind-set, and behavioural tendencies. Studies such as Onstenk (2003), Inyang and Enuoh (2009) and Phelan and Sharpley (2012) find that entrepreneurial competencies are necessary for the development and survival of an organisation.…”
Section: Literature Reviewmentioning
confidence: 99%